2021
DOI: 10.3390/agronomy11101965
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Barriers Influencing the Willingness to Adopt Technologies for Variable Rate Application of Fertiliser in Lower Austria

Abstract: Even though a broad range of technologies for variable rate application of nitrogen fertiliser is available, there are hardly any documented cases of their use in Austria. In this study, the drivers and barriers of adoption have been investigated. A survey of 242 farmers in Lower Austria was conducted. The survey covered the farmers’ economic situation, concerns, and expectations regarding the future of their farms and their interest in precision farming technologies. A choice experiment was included in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
0
0
Order By: Relevance
“…These evidences suggest that information provided explicitly through a well-known industry label or by consultants can be considered as valid support in solving asymmetric information problems and convincing potential buyers in purchasing PA equipment. In line with the results by Blasch et al ( 2021 ), our study points out the crucial role of both information provision and financial support through incentives to influence the willingness to adopt PA technologies.…”
Section: Discussionsupporting
confidence: 92%
“…These evidences suggest that information provided explicitly through a well-known industry label or by consultants can be considered as valid support in solving asymmetric information problems and convincing potential buyers in purchasing PA equipment. In line with the results by Blasch et al ( 2021 ), our study points out the crucial role of both information provision and financial support through incentives to influence the willingness to adopt PA technologies.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, 82.83% of large farmers are adopters. Such results are similar as the empirical findings of Paudel et al (2021), Kolady et al (2020), Blasch et al (2021), Paustian & Theuvsen (2017), Vecchio et al (2020b), Tamirat et al (2018).…”
Section: -Discussionsupporting
confidence: 91%
“…Only the "producers' cooperative" source of information was significantly associated with the adoption of PAT in this study. The research by Blasch et al (2021) identified that farmers most often turn to neighboring producers for information on PAT. However, the variable "other producers" had no significant effect in this study.…”
Section: -Discussionmentioning
confidence: 99%